2016
DOI: 10.1063/1.4943498
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron spectroscopy of confined carriers in CdF2-CaF2 superlattices

Abstract: Luminescence spectroscopic and temporal dynamic properties of high energy elementary excitations in CdF 2 -CaF 2 superlattices have been studied utilising excitation with vacuum ultraviolet and X-ray synchrotron radiation while comparing the results with those obtained for CdF 2 and CaF 2 bulk crystals. It is shown that the optical properties of the superlattice structures are determined by exciton emission in the CdF 2 monolayers. The experimental manifestations of exciton confinement phenomena are discussed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…As the reduced graphene oxide attaches to the surface of Ce 3+ -doped binary fluorides, it (GO) can enhance the crystal field strength, which leads to the splitting as well as shifting of the excitation peak to a higher energy side. Similarly, Reeves et al reported the optical properties of CdF 2 –CaF 2 superlattices using synchrotron spectroscopy of confined carriers and measured the exciton emission . Also in their experiment they have mentioned the exciton confinement phenomenon.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…As the reduced graphene oxide attaches to the surface of Ce 3+ -doped binary fluorides, it (GO) can enhance the crystal field strength, which leads to the splitting as well as shifting of the excitation peak to a higher energy side. Similarly, Reeves et al reported the optical properties of CdF 2 –CaF 2 superlattices using synchrotron spectroscopy of confined carriers and measured the exciton emission . Also in their experiment they have mentioned the exciton confinement phenomenon.…”
Section: Resultsmentioning
confidence: 95%
“…In semiconductors, size-dependent photoluminescence properties are found due to the quantum-confinement effect. 55 Consequently, excitation and emission bands are significantly shifted on varying the size of the particles. However, except the Ce 3+ ion, other RE 3+ -doped nanoparticles show size-independent photoluminescence behavior due to their f-f electronic transition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…СР, сформированные на основе фторидов кадмия, перспективны в плане их использования при изготовлении туннельных диодов и каскадных лазеров [6].…”
unclassified